Provocative Questions in Behavioral Medicine and the Acceleration of our Science - Diefenbach, Michael A (Ann Behav Med, 2021)
A visioning initiative among members of SBM has identified new areas of investigations, such as behavioral medicine’s need to address climate change, gun violence and science communication. These areas emerged along-side traditional areas of behavioral medicine such as decreasing health inequity and integrating behavioral medicine into health care systems.